The matrix effect on the quasi-three-level neodymium laser parameters in the stationary regime - Stashkevich, Ihar V.; Herasimenka, Valeryja I. (Journal of the Belarusian State University. Physics, 2017)
The analysis of the output characteristics of a neodymium laser with a quasi-three-level scheme for most common crystalline matrices is presented. The matrix containing neodymium ions governs the basic parameters of an active medium: the value of Stark level splitting, lifetime of the excited state, maximal concentration of neodymium ions, absorption and emission cross-sections. The energy characteristics of radiation from such a laser with different matrices in the stationary mode of generation have been studied theoretically. The modeling has been performed for an end-pumped laser. It has been shown that the efficiency is at maximum for a neodymium laser with potassium-gaddinium tungstate (KGW) matrix, it is lowering for gadolinium and yttrium vanadates, being minimal for the matrices of yttrium oxide, yttrium aluminium perovskit (YAP), and gadolinium gallium garnet (GGG). The lowest lasing threshold is characteristic for lasers with yttrium aluminium garnet (YAG) and gadolinium vanadate (GVO) matrices.
Keywords: neodymium laser; quasi-three-level scheme; efficiency; lasing threshold; Nd : KGW; Nd : GVO; Nd : YVO; Nd : YAG; Nd : YAP; Nd : GGG; Nd : Y2O3